Evaluation of Somaclonal Variations for Quantitative Traits in Fodder Sorghum - Jayaramachandran, M.; Kumaravadivel, N.; Kandasamy, G.; Eapen, Susan (International Journal of Bio-resource and Stress Management, 2023)
Through in vitro culture studies, suitable explant and combination of phytohormones were standardized for maximum frequency of callus induction and regeneration in fodder sorghum variety CO (FS) 29. The in vitro derived plants were forwarded to the field as SC2 generation (somaclones) by selfing the SC1 generation for the evaluation of somaclonal variations in quantitative characters. The somaclone (SC2) lines recorded extensive variations for quantitative traits viz., plant height, days to 50% flowering, number of tillers plant-1, number of leaves plant-1, leaf length, leaf breadth, panicle length, grain yield plant-1 and green fodder yield plant-1. Somaclone lines were critically analysed for genetic parameters and scope for improvement of green fodder yield plant-1 is discussed.